Optimized protocol for the preparation of single cells from cutaneous wounds for flow cytometric cell sorting and analysis of macrophages - Shakya, Sajina (MethodsX, 2020)
The incidence of chronic, non-healing skin wounds is accelerating, largely due to the epidemic of obesity-related Type 2 diabetes. Abnormal inflammation in wounds contributes to delayed healing. During wound repair, blood monocytes are recruited into the wound bed where they differentiate into macrophages that secrete cytokines and regulate subsequent repair events. Because the study of wound macrophages via immunohistochemistry is often unsatisfactory due to nonspecific antibody staining, the ability to isolate and analyze single cells is important for determining the phenotypes of the wound macrophages. In this article, we have expanded upon a protocol originally described by Wilson et al, 2002 [1], and optimized it for isolation of large numbers of viable macrophages from murine skin wounds that are suitable for flow cytometric cell sorting or analysis. Several parameters were found to be critical for improved macrophage yields, including: (1) The proper amount of starting material (skin tissue); (2) The optimal time for addition of Brefeldin A during enzymatic digestion; (3) Revamped guidelines for centrifugation to maximize cell pellet recovery. This optimized protocol could be further modified to perform cell sorting and flow-based immunophenotyping of any cell type involved in wound healing and inflammation.